The sustainability generation : the politics of change & why personal accountability is essential now! - Coleman, Mark C. (SelectBooks, Inc., 2012)
"Examines how indulgences from individual and generational entitlement impact the environment and society, resulting in depletion of natural resources to the detriment of future generations' ability to meet their needs. Presents options for change to rally the emerging Sustainability Generation to take action toward a more balanced, sustainable future"--Provided by publisher.